Bremsstrahlung from Relativistic Heavy Ions in a Fixed Target Experiment at the LHC - Rune E. Mikkelsen; Allan H. Sørensen; Ulrik I. Uggerhøj (Advances in High Energy Physics)
We calculate the emission of bremsstrahlung from lead and argon ions in ultraperipheral collisions in a fixed target experiment (AFTER) that uses the LHC beams. With nuclear charges of Ze equal to 82e and 18e, respectively, these ions are accelerated to energies of 7 Tev × Z. The bremsstrahlung peaks around ≈100 GeV and the spectrum exposes the nuclear structure of the incoming ion. The peak structure is significantly different from the flat power spectrum pertaining to a point charge. Photons are predominantly emitted within an angle of 1/γ to the direction of ion propagation. Our calculations are based on the Weizsäcker-Williams method of virtual quanta with application of existing experimental data on photonuclear interactions.